Corporate sustainability in international comparison : state of practice, opportunities and challenges - Windolph, Sarah Elena; Harms, Dorli; Horisch, Jacob; Schaltegger, Stefan (Eco-Efficiency in Industry and Science, 2014)
Although every country is distinguished by its history, culture and language as well as its unique economic, environmental and social conditions, it can be expected that international operating companies will exhibit common patterns since sustainability challenges do not stop at national borders. Building on original data based on results of the International Corporate Sustainability Barometer survey, this book depicts and analyzes the current state of corporate sustainability management and corporate social responsibility. Part I describes the approach and summarizes the broad results, outlining the methodology and offering an overview of results of the ICSB survey. Part II presents specific findings for each of eleven countries surveyed: Australia, Belgium, France, Germany, Hungary, Japan, Korea, Spain, Switzerland, the United Kingdom and the USA. Part III provides a comparative analysis and highlights broad patterns in the international results. Most strikingly, the book reveals surprisingly widespread similarities among the sustainability management practices of large companies in economically developed countries all over the world. All the survey results are analyzed according to the same Triple-I approach: Intention  - Why do companies manage sustainability?;  Integration - To what extent do companies embed sustainability in their core business and in their organization?; and Implementation - How is corporate sustainability operationalized? Based on this structure the analysis serves not only to make comparisons and to investigate national characteristics; it also builds a foundation for examining whether there truly is a world-spanning common state of the art of corporate sustainability. Distinguished authors who were involved in the International Corporate Sustainability Barometer project offer their insights, identifying and discussing national and international patterns that can provide the basis for further ideas and inspiration to practitioners and researchers worldwide who are engaged in corporate sustainability.